Tradução e adaptação transcultural para o português do instrumento “Behavior Rating Inventory of Executive Function” - Carim, Daniela de Bustamante [UNIFESP] (2010)
Behavior Rating Inventory of Executive Function (BRIEF) is an instrument that assesses executive functions, reflecting daily life aspects of children and teenagers aged between 5 and 18 years old. It has three versions, that is, the parenting scale, the teachers’ scale and a personal version. The purpose of this study was to translate and to adapt, into Brazilian Portuguese, BRIEF, as well as to analyze the initial psychometric properties. The translation and adaptation process followed the steps recommended in literature and widely endorsed by International Test Commission (ITC). To analyze the adaptation’s adequacy, as well as the psychometric properties, two pilot studies were carried out, and the final version was administered to a sample comprised of 277 parents, being 59.6% female, 282 teachers, being 57.4% female, 112 personal, being 63.4% female. The Cronbach’s Alpha values, assessing internal consistency for the main items of the parents’ questionnaire ranged from 0.901 to 0.945, the ones concerning the teachers’ questionnaire ranged from 0.915 to 0.959 and those concerning the personal questionnaire ranged from 0.924 and 0.957, showing proper coefficients of test’s trustworthiness. The factorial analysis of main component extracted two factors (Factor 1: Metacognition; Factor 2: Behavior Regulation). In the parents’ questionnaire, both factors were correlated (r=0.56). In the teachers’ questionnaire, correlation was 0.400, and in the personal questionnaire correlation was 0.70. The values found in the Brazilian version are similar to those reported in the original version, showing good internal consistency of the instrument in the three versions.